2020
DOI: 10.1016/j.envsoft.2020.104733
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic parameterisation and calibration approach to model hydrology and water quality of agricultural landscapes and catchments

Abstract: A pragmatic parameterisation and calibration approach to model hydrology and water quality of agricultural landscapes and catchments, Environmental Modelling and Software (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Further model refinement could focus on constraining the upper simulation values throughout the model. A qualitative "reasonable fit" visual inspection has been shown to be an effective means of assessing model performance using diverse incomplete data sets (Ghahramani et al, 2020). Ghahramani et al (2020) found that the ranking of confidence in model predictions between determinands was related to data availability as much as to the model itself, with pesticide simulations performing less well than those for hydrology, sediments, and phosphorus.…”
Section: Model Validationmentioning
confidence: 99%
“…Further model refinement could focus on constraining the upper simulation values throughout the model. A qualitative "reasonable fit" visual inspection has been shown to be an effective means of assessing model performance using diverse incomplete data sets (Ghahramani et al, 2020). Ghahramani et al (2020) found that the ranking of confidence in model predictions between determinands was related to data availability as much as to the model itself, with pesticide simulations performing less well than those for hydrology, sediments, and phosphorus.…”
Section: Model Validationmentioning
confidence: 99%
“…The program uses monitoring and modelling tools at the paddock, catchment and marine scale to enable reporting in the short-to-medium term (Waterhouse 2018). The findings from studies such as the Brigalow Catchment Study are extrapolated across subcatchments by using models such as HowLeaky and APSIM (Keating et al 2003;Ghahramani et al 2020). The outputs are then aggregated and routed to the basin outlet by using the Great Barrier Reef Dynamic SedNet model (McCloskey et al 2021b).…”
Section: How Representative Is the Brigalow Catchment Study Of The Fi...mentioning
confidence: 99%
“…Unlike deterministic modelling approaches that use quantitative parameters and initial conditions to simulate outputs [24], BBNs use probabilistic expressions to characterize the strength of the relationships between variables [25,26]. This means that BBNs can incorporate both quantitative and qualitative information, as well as information of variable quality, such as subjective assessments (e.g., expert opinion) of the probability that a particular outcome will occur, where data may be limiting.…”
Section: Bayesian Belief Network Modelsmentioning
confidence: 99%
“…A BBN model that is established from expert opinion and the published literature can be improved by incorporating additional available datasets to calibrate the CPTs [56,57] as new data become available over time. The Dirichlet distribution for CPT columns intuitively interprets the combined data (expert beliefs and observed data) [58]; however, considering the small number of available datasets, we applied a manual calibration [24]. To do this, the CPTs of the initial expert-elicited BBN model were updated, where possible, from the available spoil characteristics and environmental covariates using the Lake Lindsay site data collected 18 months post treatment (Figure 5).…”
Section: Updating Of Cptsmentioning
confidence: 99%